Pengaruh Orientasi Serat Terhadap Kekuatan Tarik Pada Composite Sandwich dengan Foam Core - Alis Ratuningtyas; Lilies Esthi Riyanti; Herwanto, Djoko (Langit Biru: Jurnal Ilmiah Aviasi, 2023)
The sandwich composites consist of the main arrangement of core and skin, widely used in aircraft structures because they have superior strength and are lighter than aluminum. This study examines the effect of fiber orientation of sandwich composite panels with foam core in three specimens on tensile load. The skin consists of kevlar, fiberglass, and carbon with various fiber orientations and all specimens were tested using ASTM E8/E8M. From the tensile test results, specimen 1 showed the best material properties with an arrangement of 0o fiberglass, 90o fiberglass, 45o fiberglass, foam core, 45o kevlar, 90o carbon, and 0o fiberglass. Specimen 1 has the highest ultimate tensile strength value of 145.5 MPa, yield strength value of 108 MPa, elongation value of 2.5%, and fracture strength value of 2.56 MPa.